2005
DOI: 10.1152/ajpheart.00781.2004
|View full text |Cite
|
Sign up to set email alerts
|

Revealing anti-inflammatory mechanisms of soy isoflavones by flow: modulation of leukocyte-endothelial cell interactions

Abstract: The antiatherogenic effects of soy isoflavone consumption have been demonstrated in a variety of studies. However, the mechanisms involved remain poorly defined. Adhesion of monocytes to vascular endothelial cells is a key step within the inflammatory cascade that leads to atherogenesis. Many factors, including the physical forces associated with blood flow, regulate this process. Using an in vitro flow assay, we report that genistein, a principal component of most isoflavone preparations, inhibits monocyte ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 51 publications
4
64
0
Order By: Relevance
“…Primary human monocytes were isolated using histopaque density gradients from healthy volunteers according to Institutional IRB approved protocols as previously described (20). Cell Tracker Green (CMFDA, C2925) fluorescent dye was purchased from Molecular Probes Inc., Eugene, OR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary human monocytes were isolated using histopaque density gradients from healthy volunteers according to Institutional IRB approved protocols as previously described (20). Cell Tracker Green (CMFDA, C2925) fluorescent dye was purchased from Molecular Probes Inc., Eugene, OR.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture and Viability-HUVEC and HAEC were cultured as previously described (20) and used between passages 3 and 7. All experiments were performed within 1 day of cells reaching confluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isoflavones, genistein, daidzein, and glycitein (and their respective glycosides), found in soy foods have anti-inflammatory properties (Chacko et al 2005;Wei et al 1995), but this has not been confirmed in uncomplicated HTN (prehypertension/Stage I HTN). Genistein has been shown to have a potent anti-inflammatory action via inhibiting monocyte adhesion to cytokine-activated endothelial cells (Chako et al 2005).…”
Section: Significance and Strengthsmentioning
confidence: 99%
“…The isoflavones found in soy foods, genistein, daidzein, and glycitein (and their respective glycosides), have been reported to have anti-inflammatory properties (Chacko et al 2005;Wei et al 1995). Atteritano et al (2007) supplemented postmenopausal women with 54 mg/day of genistein for 2 years and found sVCAM-1 and sICAM-1 to be significantly (P < 0.05) reduced compared to placebo.…”
Section: Cell Adhesion Molecule Expressionmentioning
confidence: 99%